2021
DOI: 10.1177/10499091211008431
|View full text |Cite
|
Sign up to set email alerts
|

Lean Into the Uncomfortable: Using Trauma-Informed Care to Engage in Shared Decision-Making With Racial Minorities With Hematologic Malignancies

Abstract: Discussions involving racial health disparities must include pathways for engaging in shared decision-making with racial/ethnic minorities. Research demonstrates glaring racial and ethnic disparities when it comes to hematologic malignancies from the time of diagnosis to treatment and even at the end of life. Unfortunately, decision-making in these circumstances may be streamlined, given the urgency of the disease, prognostic uncertainty, and varying treatment options. Being diagnosed with cancer is undoubtedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Critical approaches to research, such as PHCRP, bring race consciousness and equity to the forefront while illuminating disciplinary conventions within research that reinforce and perpetuate stigma and inequities . For example, a critical approach to improving patient-clinician communication among Black patients who are multiply oppressed may use trauma-informed approaches focused less on goals of care and more on supporting compassionate and nonjudgmental communication to build trust in individual clinicians, empower patients, balance power dynamics, and improve transparency …”
Section: Discussionmentioning
confidence: 99%
“…Critical approaches to research, such as PHCRP, bring race consciousness and equity to the forefront while illuminating disciplinary conventions within research that reinforce and perpetuate stigma and inequities . For example, a critical approach to improving patient-clinician communication among Black patients who are multiply oppressed may use trauma-informed approaches focused less on goals of care and more on supporting compassionate and nonjudgmental communication to build trust in individual clinicians, empower patients, balance power dynamics, and improve transparency …”
Section: Discussionmentioning
confidence: 99%
“… 9 , 29 , 30 Moreover, offering palliative care at home would particularly expand such care to minorities whose attitudes are usually against placing their loved ones in institutions. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…9,29,30 Moreover, offering palliative care at home would particularly expand such care to minorities whose attitudes are usually against placing their loved ones in institutions. 30,31 Policy Implications. Current data have indicated that even during the COVID-19 pandemic, patients and providers were not interested in remote-only palliative care delivery, particularly during the first consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four studies agreed that the use of TIC could minimize the risk of re-traumatization occurring (Dhawan & LeBlanc, 2022;Kohler et al, 2021;Lawson & Lawson, 2018;Niebauer et al, 2021). Examples of avoiding re-traumatization included the creation of a safe environment and mitigation of racial disparities by hematologists (Dhawan & LeBlanc, 2022), the empowerment of patients during cervical cancer screening to have control to stop an exam (Kohler et al, 2021), and the alleviation of stress in breast cancer patients through the provision of psychosocial support (Niebauer et al, 2021). The utility of TIC was anticipated across forms of trauma, types of cancer, and care settings.…”
Section: Effectiveness and Feasibility Of Ticmentioning
confidence: 99%
“…Both Kazak et al (2005Kazak et al ( , 2006 agreed that the use of TIC interventions should be brief, competency-based, non-stigmatizing, and aimed at the individual needs of the patients and their families. Furthermore, four studies agreed that the use of TIC could minimize the risk of re-traumatization occurring (Dhawan & LeBlanc, 2022;Kohler et al, 2021;Lawson & Lawson, 2018;Niebauer et al, 2021). Examples of avoiding re-traumatization included the creation of a safe environment and mitigation of racial disparities by hematologists (Dhawan & LeBlanc, 2022), the empowerment of patients during cervical cancer screening to have control to stop an exam (Kohler et al, 2021), and the alleviation of stress in breast cancer patients through the provision of psychosocial support (Niebauer et al, 2021).…”
Section: Effectiveness and Feasibility Of Ticmentioning
confidence: 99%